Tcrd Rearrangement Redirects a Processive Tcra Recombination Program to Expand the Tcra Repertoire - Zachary M. Carico; Kingshuk Roy Choudhury; Baojun Zhang; Yuan Zhuang; Michael S. Krangel (Cell Reports, 2017)
Adaptive immunity depends on diverse T cell receptor repertoires generated by variable, diversity, and joining (V[D]J) recombination. Here, we define the principles by which combinatorial diversity is generated in the murine Tcra repertoire. Tcra and Tcrd gene segments share the Tcra-Tcrd locus, with interspersed Vα and Vδ segments undergoing Vδ-Dδ-Jδ rearrangement in CD4−CD8− thymocytes and then multiple rounds of Vα-Jα rearrangement in CD4+CD8+ thymocytes. We document stepwise, highly coordinated proximal-to-distal progressions of Vα and Jα use on individual Tcra alleles, limiting combinatorial diversity. This behavior is supported by an extended chromatin conformation in CD4+CD8+ thymocytes, with only nearby Vα and Jα segments contacting each other. Tcrd rearrangements can use distal Vδ segments due to a contracted Tcra-Tcrd conformation in CD4−CD8− thymocytes. These rearrangements expand the Tcra repertoire by truncating the Vα array to permit otherwise disfavored Vα-Jα combinations. Therefore, recombination events at two developmental stages with distinct chromatin conformations synergize to promote Tcra repertoire diversity.